Hydrogen sensors based on zinc oxide nanoparticles - Thanittha Samerjai (2018)
Pure ZnO, pure MgO and 5 wt%MgO/ZnO nanocomposites were produced by flame spray pyrolysis (FSP) in a single step using zinc naphthenate and magnesium acetate tetrahydrate as Zn and Mg precursors. The particle properties were analyzed by XRD, BET and TEM analyses. The sensing films were prepared by mixing the nanoparticles into an organic paste composed of ethyl cellulose and terpineol as a vehicle binder and solvent, respectively. The resulting paste was spin-coated on Al2O3 substrates interdigitated Au electrodes. The gas sensing of H2 concentration ranging from 0.5-1 vol% was studied at 300oC in dry air. The 5 wt% MgO/ZnO nanocomposites film showed higher sensitivity. The sensitivity increased and the response time decreased with increasing H2 concentrations. ©2010 IEEE.